Dietary and Lifestyle Factors Associated With Metabolic Syndrome in Urban Middle-Aged Women of Babol City, Mazandaran Province, Iran - Delavar, Mouloud Agajani (2009)
Metabolic syndrome is a cluster of interconnected cardiovascular risk factors. Existing data suggest that it has reached an alarming rate, and it is found more common in women than in men. Obesity plays a central role in metabolic syndrome and it has become a common factor among Iranian women. Accordingly, it is important to elucidate both lifestyle and dietary factors to the development of metabolic syndrome among middle-aged women so as to prevent and manage the syndrome in a much better way. The research design of the present thesis was a population-based cross-sectional study, and the criteria by the NCEP ATP III were used to classify subjects with metabolic syndrome. Meanwhile, their physical activities were measured using the original International Physical Activity Questionnaires Long form. Food frequency questionnaire (FFQ) was also used in assessing individual’s habitual intake. A total of 984 individuals, aged 30-50 year old from fourteen active urban primary healthcare centres in Babol (Iran), were selected using a systematic random sampling method and sampling proportionate to size. Thus, lifestyle factors associated with metabolic syndrome were analyzed. Among the Babolian middle-aged women living in the urban area, the prevalence of metabolic syndrome was found to be 31.0 %. Overweight and abdominal obesity were also observed, and these were found around 38.0 % and 76.6 %, respectively. Older age, higher waist circumference, higher systolic and diastolic blood pressure, low education level, housewife and occupation (technician) were found to be associated with the increased odds of metabolic syndrome. Nevertheless, the adjusted odds ratio (OR) showed no significant associations between metabolic syndrome and smoking or the exposure to cigarette smoking. The moderate intensity of the physical activities was positively associated with systolic blood pressure (rho=0.07, p=0.03), cholesterol (rho=0.07, p=0.04), and triglyceride (rho=0.67, p=0.04). Meanwhile, vigorous physical activity was inversely correlated with waist circumference (rho=-0.07, p=0.04). Their total physical activity was found to be positively correlated with triglyceride (rho=0.09, p= 0.01), but was inversely correlated with HDL-cholesterol (rho=-0.07, p=0.04). The chi-square test did not reveal any statistically significant difference in the levels of the physical activities between these women, either with or without metabolic syndrome. The mean total kilocalories consumed per day were 2965. The study also suggests that a good dietary pattern which is rich in fruit, legumes, vegetables, cereals, and fish (component 1), as well as the high intakes of dairy products and eggs (component 4) decrease the likelihood of metabolic syndrome. The adjusted OR for metabolic syndrome in women with low fat intake was significantly higher than in those women with high and moderate fat intake (OR=2.923; 95% CI=1.36, 6.28). The risk of metabolic syndrome for women in the first quartile category of calcium was found to be higher than those in the highest quartile (OR=13.200; 95% CI =7.94, 21.93), and in the lowest category of black tea was indicated as lower than those in the highest categories (OR=0.181; 95% CI =0.11, 0.31). The findings of the present study indicated that a high prevalence of obesity and metabolic syndrome was identified among the middle-aged women, making this syndrome one of the major public health problems in Babol. Therefore, it is necessary to emphasize on the benefits of lifestyle modifications, including weight loss, and the intakes or consumption of more fruit, legumes, vegetables, cereals, fish, dairy products, and the increase in the intakes of food containing calcium in reducing the risk of metabolic syndrome.